Land Rights, Land Ownership, and Land Governance among Rural Communities in River Tana County, Kenya: A Gender Perspective - Wilson Ndenyele; Marie-Emmanuelle; Halimu Suleimani Shauri; Godffrey Nato (African Journal on Land Policy and Geospatial Sciences)
ontext and background